Technocratic attitudes and voting behaviour ten years after the Eurozone crisis: Evidence from the 2019 EP elections. (April 2021) - Heyne, Lea; Lobo, Marina Costa
Abstract: The onset of the Great Recession raised the profile of technocracy, or government by experts, as a contrasting model to democracy. Yet, there is little research on how attitudes towards technocracy may impact European citizens' political behaviour. Moreover, the consistency of technocracy supporters' political attitudes, especially towards the EU, is questionable. This paper uses new survey panel data collected before and after the European parliament elections in May 2019 in six countries (Belgium, Germany, Greece, Ireland, Portugal and Spain). We investigate how citizens' technocratic attitudes affect their voting behaviour in the European elections. We find evidence that citizens with technocratic attitudes are less likely to support mainstream parties, and tend to either abstain or, if they vote, to give their vote to anti-system parties, especially from the populist right. In addition, by distinguishing technocracy supporters according to their partisanship, we conclude that technocracy is a thin ideology that can be combined with different patterns of political support: while many technocracy supporters have no party identification or support non-mainstream parties and show dissatisfaction with democracy and the EU, another subgroup of technocracy supporters identifies with a mainstream political party and show above average political support and support for the EU.